THE ROLE OF CUSTOMER SATISFACTION MEDIATES THE EFFECT OF SERVICE QUALITY AND E-WOM ON MARKETPLACE REUSE INTENTIONS: A COMPARATIVE STUDY OF TOKOPEDIA AND SHOPEE - Dewi N.N.K.A.; Suprapti N.W.S. (Eurasia: Economics & Business, 2023)
The Tokopedia and Shopee marketplaces have become a phenomenon in online shopping because they managed to gain and maintain their positions at the top, beating other marketplaces that first appeared in Indonesia. This study aims to determine the effect of service quality and E-WOM on the Intention to reuse through the satisfaction of Tokopedia and Shopee marketplace users and to determine whether there is a comparison of service quality, E-WOM, customer satisfaction, and Intention to reuse Tokopedia and Shopee, marketplace customers. The number of samples taken was 160 respondents to the Tokopedia and Shopee marketplace customers, using purposive sampling. Data was collected by distributing questionnaires. The analysis technique used was SEM based on PLS and supported by VAF. The different test T-test (independent sample T-test) was used to test hypotheses about the differences between the two populations. The results of the study found that service quality and E-WOM have a positive and significant effect on customer satisfaction, service quality has a positive and not significant effect on reuse intentions, E-WOM and customer satisfaction have a positive and significant effect on reuse intentions, and customer satisfaction positively and has a significant role in mediating the effect of service quality and E-WOM on the Intention to reuse the Tokopedia and Shopee marketplaces. The study's results also found differences in E-WOM and customer satisfaction in the Tokopedia and Shopee marketplaces. In addition, it was found that there were no differences in service quality and Intention to reuse the Tokopedia and Shopee marketplaces.